Operationalizing Anti-Racism Accountability with Equitable Admissions in Nursing Education Accreditation - Alicia Swartz; Denise Dawkins; Claire Valderama-Wallace; Michelle DeCoux Hampton (Mary Ann Liebert, 2024)
For decades, health professional organizations have recommended increased diversity in the workforce and education. To address persistent inequities in health care, the racial composition of the nursing workforce needs be congruent with the U.S. population. Without first addressing structural inequity in nursing education programs, the nursing profession cannot begin to address structural racism in health care. The lack of nursing student diversity is reflective of barriers in program admissions. This article is a call to nursing accreditation bodies to operationalize anti-racism to improve U.S. nursing workforce diversity by introducing accountability structures that require evidence-based holistic admission review and analysis of admission data to ensure that student cohorts are diverse across nursing programs, thereby ensuring a future workforce that reflects the diversity of the U.S. population.